Akuntabilitas Laporan Keuangan Pesantren: Tinjauan Pemahaman Akuntansi Syariah, Kompetensi Sumber Daya Manusia - Putri Lerisa A R Y; Dede Riswandi (Tangible Journal, 2026)
This study aims to determine the level of understanding and competence of human resources towards the accountability of Islamic boarding school financial reports in Garut Regency. Using an associative quantitative method with a population of 1,477 Islamic boarding schools in Garut Regency by determining a sample using the Slovin formula of 93 respondents. The results of the study show that understanding of sharia accounting and human resource competence have a significant partial effect on the accountability of Islamic boarding school financial reports in Garut Regency.